2015
DOI: 10.1002/cam4.520
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of melinjo (Gnetum gnemon L.) seed extract in human and murine tumor models in vitro and in a colon‐26 tumor‐bearing mouse model in vivo

Abstract: Melinjo (Gnetum gnemon L.) seed extract (MSE) and its active ingredient gnetin C (GC), a resveratrol dimer, have been shown to possess a broad spectrum of pharmacological activities. In this study, we investigated the antitumor activity of MSE and GC using human and murine tumor cell culture models in vitro. The antitumor activity of GC was compared with trans-resveratrol (tRV), a stilbenoid polyphenol. Our results show that MSE and GC at clinically achievable concentrations significantly inhibited the prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 50 publications
2
54
0
1
Order By: Relevance
“…MSE and gnetin‐C induced apoptosis in all tested tumor cells but were not toxic to nonmalignant cells. In the same study, the oral administration of MSE significantly inhibited tumor growth, intratumoral angiogenesis, and the development of liver metastases in mice bearing colon‐26 tumors …”
Section: Gnetin‐cmentioning
confidence: 99%
“…MSE and gnetin‐C induced apoptosis in all tested tumor cells but were not toxic to nonmalignant cells. In the same study, the oral administration of MSE significantly inhibited tumor growth, intratumoral angiogenesis, and the development of liver metastases in mice bearing colon‐26 tumors …”
Section: Gnetin‐cmentioning
confidence: 99%
“…Melinjo is widely available and consumed in large quantities in Indonesia. 1 Hydrolyzed-proteins of melinjo seed had been proven to lower blood pressure of hypertensive rats.…”
Section: Introductionmentioning
confidence: 99%
“…Melinjo seeds are part of the Indonesian cuisine due to their high nutritive value. In fact, melinjo seed extracts are also now sold in Japan as nutritional supplement (Narayanan et al, ). Plants in this family are used in folkloric treatments for diabetes, arthritis, and bronchitis (Ota et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Plants in this family are used in folkloric treatments for diabetes, arthritis, and bronchitis (Ota et al, ). It was reported that oral administration of melinjo seed extracts does not produce significant adverse effects to laboratory animals or humans (Narayanan et al, ) and oral administration of 1000 mg/kg per day of melinjo seed extracts in rats had no observed adverse effect level (Tatefuji et al, ). Resveratrol extracted from melinjo seeds was reported to have antiangiogenic effects; inhibitory effects against endothelial senescence, tyrosinase activity, and melanin biosynthesis; and cancer preventive effects (Kunimasa et al, ; Yanagihara et al, ; Ota et al, ).…”
Section: Introductionmentioning
confidence: 99%